已知数列{an}满足a1=1,an+1=(1+cos2
(1)求a2,a3,a4,并求出数列{an}的通项公式; (2)设bn=
|
(1)a2=(1+0)a1+1=2,a3=(1+1)a2+0=4,a4=(1+0)a3+1=5,
∵an+1=
,∴an+1 (n=2m-1,m∈N+) 2an(n=2m,m∈N+) a2m+1=2a2m a2m=a2m-1+1
∴a2m+1=2a2m-1+2,∴a2m+1+2=2(a2m-1+2),∴
=2a2m+1+2 a2m-1+2
∴数列{a2m-1+2}是公比为2的等比数列,∴a2m-1+2=(a1+2)2m-1,
∴a2m-1=-2+3•2m-1(m∈N+),a2m=
a2m+1=-1+3•2m-1(m∈N+),1 2
∴an=
=-2+3•2
-1n+1 2 -1+3•2
-1n 2
=-2+3•2
-1(n为奇数)n+1 2 -1+3•2
-1 (n为偶数)n 2
.-2+3•2
(n为奇数)n-1 2 -1+3•2
(n为偶数)n-2 2
(2)bn=
=1+-1+3•2n-1 -2+3•2n-1
=1+1 -2+3•2n-1
,1 2(-1+3•2n-2)
①当n=1时,S1=b1=2≤1+
,不等式成立;5 3
②当n≥2时,-1+3•2n-2≥2,∴0<
<1,1 -1+3•2n-2
∵0<
<1 -1+3•2n-2
=1+1 (-1+3•2n-2)+1 2 3•2n-2
∴
<1 2(-1+3•2n-2) 1 3•2n-2
∴bn<1+
=1+1 3•2n-2 4 3•2n
∴Sn<2+(1+
)+(1+4 3•22
)+…+(1+4 3•23
)4 3•2n
=n+1+
×4 3
(1-1 4 1- 1 2
)=n+1+1 2n-1
(1-2 3
)1 2n-1
=n+
-5 3
<n+4 3•2n 5 3
由①②知:Sn≤n+
.5 3